IFPRI Report: Agriculture can give a helping hand to cities [Feature article] - Garrett, James L. (International Food Policy Research Institute, 1996)
Commentary: Agriculture Can Give a Helping Hand to Cities; Roundtable Workshop Marks Beginning of Urban Food and Nutrition Study in Ghana; Research in North Africa and West Asia to Benefit Farmers on Fragile Lands; Ecoregional Mapping Helps Pinpoint Areas Prone to Malnutrition; Why Are Diets Changing in Asia?; New Booklet Spreads the 2020 Vision to Broader Audiences; Policies Aim to Avoid Conflict Over Dwindling Natural Resources; 2020 Vision Resources Catalog Now Available; Disease and Food Security: Two New Perspectives; Indicators of Performance Quality Applied to Indian Irrigation System; Reprints